Optimization of Parquetting of the Concentrator of Photovoltaic Thermal Module - Sinitsyn, S. (Springer, 2020)
The article discusses the geometric aspects of the optimization of manufacturing a parabolic-type solar radiation concentrator, which is the main part of a solar photovoltaic thermal module. The method of three-dimensional parquetting of the surface of a parabolic concentrator is considered. To ensure the specified accuracy and smoothness of the surface bypassing at the stages of designing and manufacturing the device, a method of fan-shaped geometric parquetting of the surface of a parabolic concentrator is proposed. As an implementation of the method, a manufactured concentrator of a solar photovoltaic thermal module and illumination of the photodetector at its focus are presented. Â© 2020, Springer Nature Switzerland AG.